An Evaluation of the Effectiveness of Pain Management Interventions in the Postoperative Setting - JAMAL SIDDIQUI, SARMAD; ALI NAPER, MOHAMMAD; KALEEM, ABDUL; AHMED SHAIKH, NAVEED; MALIK, EHSANULLAH; NAZISH (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: The objective of this research is to evaluate the effectiveness of various pain management interventions in the postoperative setting and assess their impact on pain relief, patient satisfaction, and recovery outcomes Material and Methods: This prospective observational study was conducted at CMC Hospital Larkana for a period of 6 months from January 2021 to June 2021 after approval from the institutional ethics review committee. Patients aged 18 years or above, with different surgical interventions, and experiencing postoperative pain was eligible for inclusion. Patients with pre-existing chronic pain conditions or those unable to provide informed consent were excluded. Results: A total of 96 participants were selected for this study. Out of them majority of the participants were male, accounting for 63 individuals or 60.4% of the total population. Females made up 33 individuals, representing 31.6%. When examining the types of surgical procedures, the most common were urological surgeries with 25 cases (24%), followed by abdominal surgeries with 34 cases (32.6%). The least common were thoracic surgeries with only 2 cases (1.9%). The mean age of the group is 42.3 years, with a standard deviation of 10.5 years. The mean weight is 71.2 kg, with a standard deviation of 13.8 kg. The average height is 154.8 cm, with a standard deviation of 4.7 cm. The mean BMI (Body Mass Index) is 27.2 kg/m2, with a standard deviation of 4.6 kg/m2. The experience of pain is a sign that the illness has gotten worse" had a mean score of 3.2±1.4, indicating a moderate level of agreement but with more variability. Practical Implication: Effective postoperative pain management is crucial for improving patient outcomes, reducing recovery times, and enhancing overall quality of life. This research provides evidence-based insights that can inform clinical practices, ensuring that patients receive the most effective pain relief with minimal side effects. Furthermore, by identifying the most effective interventions, the study can help reduce the burden on healthcare systems through decreased hospital stays and readmissions, as well as lower the risk of chronic pain development. The findings can also guide policy makers in developing standardized pain management protocols, ultimately leading to improved patient satisfaction and healthcare efficiency. By addressing the community’s need for effective pain management, this study contributes to the well-being of postoperative patients and supports the broader goal of enhancing public health. Conclusion: We found that the implementation of various interventions significantly improved pain relief, increased patient satisfaction, and positively impacted recovery outcomes